# Ôn tập Căn bậc hai. Căn bậc ba

Rút gọn biểu thức:

a, A= $\sqrt{2-\sqrt{3}}\left(\sqrt{6}-\sqrt{2}\right)\left(2+\sqrt{3}\right)$

b, $\frac{\left(2+\sqrt{3}\right)\sqrt{2-\sqrt{3}}}{\sqrt{2}+\sqrt{3}}$

Giúp mih nhanh với ạ. Cần gấp! Cảm ơn nhiều ạ

Tân binh -
29 tháng 11 2020 lúc 22:18

a) A= $\sqrt{2-\sqrt{3}}$ $\left(\sqrt{6}-\sqrt{2}\right)$$\left(2+\sqrt{3}\right)$

A= $\sqrt{2-\sqrt{3}}$ . $\sqrt{2+\sqrt{3}}.\sqrt{2+\sqrt{3}}$ .$\left(\sqrt{6}-\sqrt{2}\right)$

A= $\sqrt{\left(2+\sqrt{3}\right)\left(2-\sqrt{3}\right)}$ . $\sqrt{2+\sqrt{3}}$ . $\sqrt{2}\left(\sqrt{3}-1\right)$

A= 1. $\sqrt{2\left(2+\sqrt{3}\right)}$ $\left(\sqrt{3}-1\right)$

A=$\sqrt{4+2\sqrt{3}}$ .$\left(\sqrt{3}-1\right)$

A=$\sqrt{\left(\sqrt{3}+1\right)^2}$ $\left(\sqrt{3}-1\right)$

A=$\left|\sqrt{3}+1\right|$$\left(\sqrt{3}-1\right)$

A=$\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)$

A=3-1

A=2

Vậy A=2

b)$\frac{\left(2+\sqrt{3}\right)\sqrt{2-\sqrt{3}}}{\sqrt{2}+\sqrt{3}}$ = $\frac{\sqrt{2+\sqrt{3}}.\sqrt{2+\sqrt{3}}.\sqrt{2-\sqrt{3}}}{\sqrt{2}+\sqrt{3}}$ = $\frac{\sqrt{2+\sqrt{3}}.\sqrt{\left(2+\sqrt{3}\right)\left(2-\sqrt{3}\right)}}{\sqrt{2}+\sqrt{3}}$=$\frac{\sqrt{2+\sqrt{3}}.1}{\sqrt{2}+\sqrt{3}}$ = $\frac{\sqrt{2+\sqrt{3}}}{\sqrt{2}+\sqrt{3}}$ .

Bình luận (0)

Các câu hỏi tương tự